2017
DOI: 10.1080/00015385.2017.1335454
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic recovery after strength exercise in lower and upper limbs

Abstract: Introduction Strength exercises influence the cardiovascular system by promoting autonomic adjustments induced by the increased metabolic demand and consequent increase in local blood flow. However, it is unclear whether there are differences between upper and lower limbs. We aimedto evaluate recovery of cardiac autonomic modulation afterstrengthexercise in upper and lower limbs. Methods We analysed 29 healthy male subjects physically active but not professional athletes aged between 20 and 35 years old. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…However, the study by Bellavere et al (2018) showed that after HE for 4 months, the LF/HF ratio of subjects with type II diabetes decreased. The transient high-intensity resistance training proposed by Isidoro et al (2017) also showed a decreased LF/HF ratio. The difference might come from different modes of exercise, which was supported by the study by Morishima et al (2018) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the study by Bellavere et al (2018) showed that after HE for 4 months, the LF/HF ratio of subjects with type II diabetes decreased. The transient high-intensity resistance training proposed by Isidoro et al (2017) also showed a decreased LF/HF ratio. The difference might come from different modes of exercise, which was supported by the study by Morishima et al (2018) .…”
Section: Discussionmentioning
confidence: 91%
“…The possible reason of significant differences in their study was that the exercise intensity of their subjects was 10% higher than ours, and the subjects must exercise to exhaustion in the last set. The article by Isidoro et al (2017) on healthy men aged 20–35 years also showed that transient high intensity resistant exercises could reduce RMSSD significantly. The difference between their and our results might come from the fact that all limbs of subjects in their research should exercise and the total exercise volume was different.…”
Section: Discussionmentioning
confidence: 96%
“…After review, a total of 26 studies were included in the systematic review and meta-analysis. 14 , 15 , 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 52 , 53 , 54 , 55 , 56 , 57 All included articles were published between 2006 and 2019 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, as reviewed in Goldsmith, Bloomfield, and Rosenwinkel ( 2000 ), Hautala, Kiviniemi, and Tulppo (Hautala et al, 2009 ), and Seals et al (Seals et al, 2001 ), the impact of aerobic exercise on cardiac activity and BRS has widely been assessed both during and following aerobic exercise. However, fewer studies have investigated the role resistance exercise has on acute ANS activity (Heffernan et al, 2006 ; Isidoro et al, 2017 ; Mayo et al, 2016 ; Mayo et al, 2016 ). This may in part be attributable to the time constraints required to obtain valid and reliable ANS data (5‐min) (Burma, Graver, et al, 2021 ), where commonly prescribed forms of resistance exercise are not sustainable for greater than 15 repetitions (~30‐seconds).…”
Section: Introductionmentioning
confidence: 99%